Colour Doppler and Adverse Perinatal Outcomes in Pregnancies with Foetal Growth Restriction: A Prospective Longitudinal Study - Shelly Khillan; Sarbhjit Kaur (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Foetal Growth Restriction (FGR) accounts for a significant proportion of perinatal morbidity and mortality. The study was done to diagnose the foetuses “at risk”, so that timely intervention could prevent perinatal morbidity and mortality, as FGR foetuses with deranged velocimetry of Uterine Artery (UA), Umbilical Artery (UMA), Middle Cerebral Arteries (MCA) are associated with high perinatal morbidity and mortality. Aim: To evaluate the usefulness of blood flow velocimetry of UA, UMA, and MCA as well as a Cerebroplacental Ratio (CPR) on colour doppler and their prediction of adverse perinatal outcome. Materials and Methods: This was a prospective longitudinal study done in the Department of Obstetrics and Gynaecology, Government Medical College and Rajindra Hospital, Patiala, Punjab, India from October 2021 to March 2022. The study was conducted among 200 antenatal patients, who had a singleton pregnancy, irrespective of age and parity and had FGR foetuses. Blood flow velocities in the UA, UMA, MCA, and CPR were measured. Patients were divided into four groups with 50 patients in each group. Group I included FGR foetuses with normal blood velocities, group II included FGR foetuses with abnormal UA velocimetry, group III included FGR foetuses with abnormal UMA and MCA velocimetry and group IV included FGR foetuses with abnormal CPR. Adverse perinatal outcomes in the form of Respiratory Distress Syndrome (RDS), prematurity, Appearance, Pulse, Grimace, Activity and Respiration (APGAR) <7 at 5 minutes, admission to Neonatal Intensive Care Unit (NICU), and perinatal mortality were assessed in relation to these doppler blood flow patterns. Categorical variables were analysed with the help of Chi-square test and Fisher-exact Test. Continuous variables were analysed with ANOVA when data were normally distributed otherwise Kruskal Wallis H test was used. Results: The mean birth weight was 2432±423, 2209±329, 2100±223 and 1329±403 grams in Groups-I, II, III, and IV (p-value of <0.001.) The mean gestational age was 38.1±2.3, 37.3±3.2, 36±3.6 and 33.1±3.1 weeks in groups I, II, III, and IV (p-value of <0.001). Perinatal morbidity in the form of RDS and prematurity were compared among four groups with 0, 3 (6%), 17 (34%), and 39 (78%) in Groups I, II, III, and IV (p-value of <0.001). APGAR score <7 at 5 minutes was 0, 2 (4%), 9 (18%), and 13 (26%) in groups 1, II, III, and IV (p-value of <0.001). A total of 6 (12%), 16 (32%), 37 (74%) and 46 (92%) C-sections were performed in group I, II, III and IV, respectively, p-value of <0.001. Maternal mortality of 1 (2%) in group III and 2 (4%) was observed in group IV. But no maternal death was there in group I and II. Conclusion: The adverse perinatal outcomes were seen with changes in Pulsatility Index (PI) value of UA, UMA, MCA. But the patients with a deranged CPR ratio had got worse perinatal outcomes than either deranged MCA, PI or UMA PI alone. Hence, doppler ultrasound especially CPR ratio should be an integral component of routine evaluation of FGR pregnancies, as it helps in obstetrical surveillance and management, and thereby improving adverse perinatal outcomes.